The Health Services White Paper : The Labour Party's policy
1944-09 1944 1940s 22 pages - 4 - 2. Public money shall only be spent by publicly responsible bodies. It is a cardinal principle of British democratic government that public money shall only be spent by bodies which can be called to give public account of their work, through the people's elected representatives. This does not mean that the elected representatives themselves must control directly all such bodies. Indeed it is often in the public interest that the public control should be indirect, through trustees appointed by the Government, for fixed periods. This is particularly desirable where the body in question has to work reasonably impartially in the political field - for example the B.B.C. or the Universities. What cannot be admitted is that any self-appointed body, trade or profession, should, itself control the State's expenditure of money on that body, trade or profession. The danger then is that the body, trade or profession will place its own benefit above that of the public. It is right that its voice should be heard and its advice considered. But the final decisions must rest with the people's representatives. In the sphere of health, there are two powerful autonomous bodies - the medical profession and the voluntary hospitals. Each is seeking to control the expenditure of public monies on its own behalf. The White Paper plan prevents this, while giving to each powerful advisory roles, which is their proper function. The Labour Party fully supports both the principle of public responsibility, and the right of all participants in the health service to offer advice to the controlling authorities. 3. A complete health service can only be fully maintained, at any rate for many years, through the present generation of doctors, and with the existing voluntary hospitals and clinics. Let us take the doctors first. The B.M.A. has for many years urged that the panel should be extended to cover dependants of insured persons and to include specialist advice and treatment. The White Paper goes far beyond this, for it covers the whole population and every form of treatment, including full hospital treatment. The B.M.A. object particularly to the inclusion of richer people, for fear that private fees will disappear. This objection cannot be admitted for several good reasons:- (a) The burden of hospital and specialist treatment now falls most heavily on people earning between £600 and £1,200 a year. A major operation may use up a lifetime's savings, and add serious financial worry to the inevitable worries of illness. (b) Those who can afford one form of treatment may be unable to afford another, and better form. (c) If a line is drawn anywhere, above which inclusion in the scheme is forbidden - or even made voluntary - there is always the chance that someone may suddenly lose his money, and thus become eligible for benefits for which he has not contributed. (d) Social security insurance is to be universal. The full health service is a part of social security, and contributions are to entitle people to both medical and money benefits. If the health service were not universal, it would be difficult to make the social security service universal. 292/847/3/166